NOVELL NETWARE 3.12 INSTALLATION ON LOCAL AREA NETWORK (LAN) - Tri Pujiyanto; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 1999)
With the LAN network we can get information between Workstation Workstation with each other and can speed information services and can save costs compared to using a PC.With the LAN, then we can apply the multiuser applications, such as accounting systems. Some people can enter a transaction similar to the job immediately resolved. Besides, the use of Novell Netware 3:12 is very effective and efficient and easy in the install process.